A Weight Prediction Model for Electric Propulsion System applied on Light Helicopters (CS.27) - Mauri, F.L.C.; Merlo, F.; Tramontana, G. (My University, 2023)
Aim of this work is to present a possible high-level conceptual method of weight prediction to manage config-urations where an electric propulsion system is able to support the thermal engine failure to guarantee a com-plete safe landing and not only an emergency one like autorotation. Boundary conditions for this analysis are a starting failure event at an altitude of 6000ft associate with a descending/landing time of 6’ ca.
Keywords: Aircraft Design